Intraspecific variation in wing geometry among Tabanus rubidus (Diptera: Tabanidae) populations in Thailand - Chaiphongpachara, Tanawat; Weluwanarak, Thekhawet; Changbunjong, Tanasak (Frontiers in Veterinary Science, 2022)
Tabanus rubidus (Wiedemann, 1821) (Diptera: Tabanidae) is a hematophagous insect of veterinary and medical importance and is the predominant Tabanus spp. in Thailand. It is a potential mechanical vector of Trypanosoma evansi, which causes surra in domestic and wild animals. Wing geometric morphometrics is widely used as morphological markers for species identification and to assess the insect population structure. Herein, we investigated the intraspecific variation in wing geometry among T. rubidus populations in Thailand using landmark-based geometric morphometric analysis. T. rubidus females were collected from five populations in four geographical regions in Thailand. The left wings of 240 specimens were removed and digitized using 22 landmarks for analysis. While wing size variations were found between some populations, wing shape variations were detected in all. These intraspecific variations in T. rubidus populations indicate an adaptive response to the local environmental conditions.